(untitled) (Research, Society and Development, 2020)
The Activity Problem Situations Student in Mathematics is formed by the system of actions: formulating the student problem, building the conceptual nucleus, solving the student problem and interpreting the solution, in turn each action is formed by operations, with the purpose of knowing level of students in problem solving in Mathematics. This activity is based on the theories of Leontiev’s Activity, on the formation of Galperin’s mental actions and on Majmutov’s problematizing teaching. The goal is to diagnose the level of learning, in the content of addition and subtraction, through the Activity Problem Situations Student in Mathematics, of the students in the 3rd year for Elementary School students of the College of Application/UFRR. In the methodological procedures, the actions and operations of the Activity Problem Situations Student were converted into quantitative and qualitative indicators through a written diagnostic test formed by tasks with a problematizing focus. The Scheme of Base Orienting Complete of Action was used as a means of controlling the Activity Problem Situations Student. Conclude that students still have difficulties in solving problems in the content of addition and subtraction.